Characteristics of soils developed from alluvium and their potential for cocoa plant development in East Kolaka Regency, Southeast Sulawesi - E Yatno; S Sudarsono; I Iskandar; B Mulyanto (Journal of Degraded and Mining Lands Management, 2016)
Cocoa is one of plantation commodities that is quite important for the national economy. Land management for the development of this plant should pay attention to the characteristics of the soil. Three soil profiles formed from alluvium parent material  in East Kolaka Regency were investigated to determine the mineralogical, physical, and chemical soil properties, as well as the potential of the land for the development of cocoa plant. The results showed that the mineral composition of the sand fraction was dominated by quartz, while the clay mineral fraction was composed of kaolinite, hydrate halloysite, interstratified of illite-vermiculite and smectite. The soils were characterized by poor drainage, low bulk density (0.78 to 0.95 g / cm3), moderate available water pores (10-15%), slow to fast permeability (0.10 to 14.05 cm / h), silty clay loam to silty clay texture of top soil, acidic soil reaction (pH 4.62 to 5.47), high organic C content (3.86 to 4.60%) in the top soil and very low organic C content (<0.65%) in the lower layer, moderate to high available P (14-38 mg / kg) in the A horizon and very low to moderate (1-18 mg / kg) in horizon B, moderate to high P2O5 (30-71 mg / 100g) in horizon A and extremely low (1-11 mg / 100g) in horizon B, very low to moderate K2O (3-28 mg / 100g ), moderate to high exchangeable Ca (9.32 to 13.92 cmolc / kg) in the upper and lower (0.70 to 5.04 cmolc / kg) in the bottom layer, high exchangeable Mg content (2.83 to 8.95 cmolc / kg), high soil CEC (34.18 to 38.28 cmolc / kg) in the upper layer and low to moderate (7.87 to 20.39 cmolc / kg) in the bottom layer, moderate to high base saturation (44-68%), and very low to moderate Al saturation (0-17%). At the family level, the soil was classified as Fluvaquentic Endoaquepts (EK 1 profile) and Typic Endoaquepts (EK 2 and EK 3 profiles), finely loamy, mix, acid, isohypertermik. The land was marginally suitable (S3) for cocoa plant with the contraints of impeded drainage, acid soil reaction, and low K2O. Drainage channel management can be done to increase the carrying capacity of the land for the development of cocoa plant.